Teaching for Toursists on Traveling over Lie River Using Virtual Reality Application - Mei Hua; Lily Tan (International Journal of Instruction and Smart Education, 2023)
Tourism is a very important economic sector of China, for it is one of the significant device source for China. To increase the role of sustainable tourism in economic growth, promoting tourism is important to attract tourists continuously and effectively. Nowadays, promotion uses many kinds of methods and media, including using mobile devices, for the fast-growing of smartphone usage globally. Virtual Reality is considered an effective medium to convey promotional messages for tourism and is essential to promote China tourism. This research consists of six phases of VR Development, such as assignment, analysis, creation, testing, implementation, and operation,. During the assembly phase, the Virtual Reality is built using the Makar platform. The application is expected to increase tourism visits in China.